Pengembangan Model Pembelajaran Ekonomi Koperasi untuk Meningkatkan Kemampuan Berpikir Kristis Mahasiswa - Ni'matul Istiqomah; Agung Haryono; Nur Anita Yunikawati; Ainun Diesta Fidinnia (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2022)
Cooperative Economics is one of the courses within the scope of Economic Education as a basis for understanding cooperatives and the people's economy. In presenting the Cooperative Economics course, critical thinking skills are needed to understand current issues regarding people's economic problems. The purpose of this research is to develop a cooperative economic learning model to improve students' critical thinking skills through recent case studies. The development method in this study adopted the R&D model from Brog and Gall with stages; (1) Preliminary research, (2) research planning, (3) model development, (4) expert testing and implementation of field trials, (5) revision of field test results, (6) implementation of main field tests, (7) revision of results main field test, (8) due diligence, (9) final revision of due diligence results, and (10) dissemination and implementation of the final product. Furthermore, the cooperative economic learning model is applied with quite effective results with an average of 58.7376 based on the core gain analysis. These results also provide the conclusion that the development of learning models is quite effective in improving students' critical thinking skills.